Solitons in magneto-optic waveguides by extended trial function scheme - Ekici, Mehmet; Zhou, Qin; Sonmezoglu, Abdullah; Moshokoa, Seithuti P.; Ullah, Malik Zaka; Biswas, Anjan; Belic, Milivoj (Superlattices and microstructures, 2017)
This paper obtains soliton solutions to magneto-optic waveguides that appear with Kerr, power and log-law nonlinearities. The extended trial function method is employed to obtain these solutions. Thus, bright, dark and singular soliton solutions are retrieved. In addition, Gaussons are obtained for log-law nonlinear waveguides. All of these solutions appear with constraints that guarantees the existence of solitons and Gaussons. •Optical solitons in magneto-optic waveguides are studied analytically.•Soliton solutions and Gaussons are reported.•Kerr, power and log-law nonlinearities are considered.